The impact of freestyle swimming based on project based learning - Kurnia Rusli; Syamsul Bachri Thalib; Andi Ihsan; Firmansyah Dahlan (Physical Education Departement of University PGRI Jombang, 2025)
Aim to test the impact of project-based learning freestyle swimming on improving students' freestyle swimming ability. This research used the Pre-Experimental designs method with One-Group Pretest-Posttest design. The sampling technique used random sampling on the population of students who were taking swimming courses so that 16 samples were selected. The research location was one of the universities in Makassar City. Data analysis techniques for hypothesis testing used N-Gain Score (%). Result: The average N Gain Score (%) was 56% in the moderate or quite effective category. This shows that freestyle swimming based on project based learning has proven to be effective significantly in improving students' freestyle swimming abilities.